Cyanidin-3-O-glucoside Ameliorates Brain Damage by Modulating Gut Microbiota in Naturally Aging Mice - CHEN Yuyu, PENG Wenting, SONG Ge, FANG Wei, QI Wentao, WANG Yong (Shipin Kexue)
Objective: To investigate the effect of cyanidin-3-O-glucoside (C3G) on brain damage and gut microbiota in naturally aging mice. Methods: Mice aged 2 and 18 months were divided into four groups: young control, young + C3G, aging model and aged + C3G. The second and fourth groups were administered by gavage with 50 mg/kg C3G consecutively for eight weeks. The following parameters were assessed: serum levels of inflammatory factors and antioxidant indexes, expression levels of neurotrophic factors and brain damage markers in brain tissue; microbial diversity and metabolite changes in intestinal contents. Results: C3G significantly decreased the level of inflammatory factors (P < 0.05), increased the activity of antioxidant enzymes (P < 0.05), and up-regulated the expression of brain-derived neurotrophic factor (BDNF), while inhibiting the production of brain damage markers including beta amyloid 1-42 (Aβ1-42) (P < 0.05). In addition, C3G increased the relative abundance of Faecalibaculum and Bifidobacterium in the gut, while decreasing the level of Enterorhabdus. These changes in gut microbiota contributed to the production of docosahexaenoic acid and eicosapentaenoic acid and decreased linoleic acid levels (P < 0.05). Correlation analysis showed that Faecalibaculum and Bifidobacterium were negatively correlated with inflammatory factors and nerve damage indicators, but positively correlated with antioxidant capacity and neurotrophic factors. Conclusion: C3G can alleviate aging-related neurological damage and improve brain health in naturally aging mice by modulating gut microbiota. This finding may provide a theoretical basis for the development of aging-delaying health foods containing anthocyanins.